Optical electronics in modern communications - Yariv, Amnon (Oxford Univ. Press, 1997)
This book introduces readers to the first principles of phenomena and devices used in the practice of laser physics, including applications based on lasers with emphasis placed on optical fiber communications, and features real-life examples as well as extensive problems.